2016
DOI: 10.1016/j.amepre.2016.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Screening in Vulnerable Patients

Abstract: Introduction Low-income, low-literacy, limited English–proficient populations have low colorectal cancer (CRC) screening rates and experience poor patient–provider communication and decision-making processes around screening. The purpose of this study was to test the effect of a CRC screening decision aid on screening-related communication and decision making in primary care visits. Study design RCT with data collected from patients at baseline and immediately after the provider encounter. Setting/particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…Twenty-seven articles reported CRC screening preferences for a single or multiple racial/ethnic minority groups ( Table 2 ). 42 68 Out of these studies, nine were conducted among African Americans,42,44,48,49,54,57–59,61 five among Hispanics/Latinos, 47 , 53 , 55 , 62 , 68 eight among both African Americans and Hispanics/Latinos, 43 , 45 , 50 , 51 , 63 66 four among non-whites, 46 , 56 , 60 , 67 and one among Korean Americans. 52 Race was self-reported in nearly all of these articles, except for a study in which recruitment was conducted at a community-based organization serving Korean Americans, 52 a study that used health insurance claims data with enrollment database-reported race/ethnicity, 59 and a study that did not clearly specify how race/ethnicity was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven articles reported CRC screening preferences for a single or multiple racial/ethnic minority groups ( Table 2 ). 42 68 Out of these studies, nine were conducted among African Americans,42,44,48,49,54,57–59,61 five among Hispanics/Latinos, 47 , 53 , 55 , 62 , 68 eight among both African Americans and Hispanics/Latinos, 43 , 45 , 50 , 51 , 63 66 four among non-whites, 46 , 56 , 60 , 67 and one among Korean Americans. 52 Race was self-reported in nearly all of these articles, except for a study in which recruitment was conducted at a community-based organization serving Korean Americans, 52 a study that used health insurance claims data with enrollment database-reported race/ethnicity, 59 and a study that did not clearly specify how race/ethnicity was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…We used a measure of screening preferences from prior studies. 24 Participants were asked, ''If you had to choose a colon cancer screening test, which test would you prefer?'' with multiple choice response options of the different tests (i.e., FOBT/FIT and colonoscopy) and options to indicate they had no preference or did not have enough information to decide.…”
Section: Methodsmentioning
confidence: 99%
“…and they may encourage readers to reflect on the information in a structured way, for example by the means of “values clarification exercises” [ 8 ]. Studies have shown that decision aids can increase CRC knowledge and the proportion of citizens making an informed decision about screening uptake when used by citizens and healthcare professionals together [ 9 , 10 ]. Furthermore, they can increase screening uptake [ 11 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tailoring a decision aid to this group could be advantageous, but their information needs are diverse, ranging from a desire for a clear recommendation to the need to know all the details [ 25 ]. Decision aids tailored to this group do exist [ 9 , 10 , 13 ], but are not self-administered [ 19 ], and none of them embrace diverse information and support needs. Hence, this research group has developed a decision aid tailored for lower educational attainment citizens [ 26 ].…”
Section: Introductionmentioning
confidence: 99%